NWFPs in Bulungan, East Kalimantan, Indonesia - Katz, E. (1997)
This subchapter examines the NWFP trends in the area designated as the Bulungan Research Forest, which has been allocated by the Indonesian government to CIFOR for research purposes. The research forest covers 303 000 hectares in Bulungan district, East Kalimantan, between the Malinau and Bahau rivers, adjacent to the Kayan-Mentarang National Park. The NWFPs discussed include animals and birds, camphor, gaharu, gutta percha, illipe nuts, damar and rattan. The article also raises questions about how these trends and scenarios will unfold in the future in areas such as Bulungan.